Influences of the mass of boxing gloves on the impact force of a rear hand straight punch - Nakano, G.; Iino, Y.; Kojima, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this paper was to investigate the influences of the mass of boxing gloves on the impact force of a rear hand straight punch thrown into an unfixed target whose mass (4.36kg) was similar to that of the typical human head.